2007
DOI: 10.2478/s11756-007-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxonomic diversity as an indicator of ecological diversity — case study Vranica Mts in the Central Bosnia

Abstract: Syntaxonomic diversity (SD) represents the number of plant communities (phytocoenoses) in certain area. Plant communities as organized systems of populations of various coexisting plant species inhabiting same or similar habitat in the function of time. SD is one of the best indicators of the state and potential carrying capacity of every ecosystem and an attribute of total ecological diversity. In general, level of syntaxonomic diversity indicates habitat heterogeneity and diversity. This could have significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
1
31
0
7
Order By: Relevance
“…The flora and vegetation display a considerable resemblance to those of the Carpathians (Redžić 2007;Stefanović et al 2009). Of the species occurring on the Vranica Mountains whose the centre of range is to be found in the Carpathians, the most spectacular example is Leucanthemum waldsteinii (Schultz-Bip.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flora and vegetation display a considerable resemblance to those of the Carpathians (Redžić 2007;Stefanović et al 2009). Of the species occurring on the Vranica Mountains whose the centre of range is to be found in the Carpathians, the most spectacular example is Leucanthemum waldsteinii (Schultz-Bip.)…”
Section: Discussionmentioning
confidence: 99%
“…Out of the whole of the Dinaric Mountains, only on the Vranica Mountains does Carex curvula All. grow, forming an association Phyteumo confusae-Caricetum curvulae (Redžić 2007) having a very similar species composition to Primulo minimaeCaricetum curvulae from the Southern Carpathians (Coldea 1991). The latest phylogeographic studies on Carex curvula revealed a genetic uniformity of the whole eastern (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…), te iznad pojasa submontane smrčeve šume Picetum "subalpinum" (Lakušić, 1966(Lakušić, , 1970Horvat et al, 1974;Lakušić et al, 1979;Redžić, 2007Redžić, , 2011.…”
Section: Uvodunclassified
“…Snježni pokrivač je prisutan oko 180 dana godišnje. Pored temperature, za biljni pokrov je važno formativno djelovanje vjetra (Lakušić, 1970;Redžić, 2007).…”
Section: Opće Karakteristike Istraživanog Područjaunclassified
See 1 more Smart Citation